2019
DOI: 10.24071/llt.v22i1.1776
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Peer-Assessment Practice in Graduate Students� Academic Writing

Abstract: This study aims to explore the practice of peer-assessment in academic writing.The current researchers find it urgent to investigate academic writing because ithas rigid rules that can sharpen writers' critical thinking. The products ofacademic writing need to be assessed. Peer-assessment is one of alternatives usedto assess students learning outcomes and monitor students progress in the class.This research is a case study. Data were collected from the first semester students,who joined an academic writing cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This research found out that Indonesian EFL teachers are prompted to promote more pleasurable academic writing learning activities for university learners to continuously motivate them to practice their academic writing and critical thinking skills. In the second study, Dewi et al, (2019) highly encouraged Indonesian EFL teachers to utilize peer-assessment activities in their academic writing classes to help learners enrich each other's understanding more efficiently regarding academic writing conventions and increasingly improve their critical thinking skills concurrently. Husin and Nurbayani (2017) prompted Indonesian EFL teachers to continually instill more interactive academic writing activities to preserve their volition to rehearse their academic writing skills meaningfully.…”
Section: Introductionmentioning
confidence: 99%
“…This research found out that Indonesian EFL teachers are prompted to promote more pleasurable academic writing learning activities for university learners to continuously motivate them to practice their academic writing and critical thinking skills. In the second study, Dewi et al, (2019) highly encouraged Indonesian EFL teachers to utilize peer-assessment activities in their academic writing classes to help learners enrich each other's understanding more efficiently regarding academic writing conventions and increasingly improve their critical thinking skills concurrently. Husin and Nurbayani (2017) prompted Indonesian EFL teachers to continually instill more interactive academic writing activities to preserve their volition to rehearse their academic writing skills meaningfully.…”
Section: Introductionmentioning
confidence: 99%
“…The students involved in the assessment gave the score to their peers, guided by the teacher's criteria. The students' critical thinking is needed during peer assessment activities because they are required to criticize their peers' writing (Dewi et al, 2019). By involving students in assessment, teachers can enhance students' learning through showing the students as the writer to assume criteria in assessing their writing (Crusan & Matsuda, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Self-and peer-assessments are involved in the previous study, which has a powerful influence on the students. Those alternative assessments are believed to help students to write with better compositions (Dewi et al, 2019). The research by Iraji et al (2016) comparing non-experimental and experimental groups shows a significant change in the experimental group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of higher education, the practice of peerassessment in academic writing is believed to contribute to students' writing. Studies have shown that peer assessment plays an important role in the writing process (Dewi et al 2019;Casas et al 2018;Woodhouse & Wood 2020).…”
Section: Introductionmentioning
confidence: 99%